2009
DOI: 10.1007/s12032-009-9355-0
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of unicentric and multicentric Castleman’s disease: a report of 52 patients

Abstract: Castleman's disease (CD) is a rare disorder characterized by non-cancerous tumor growth that may develop in the lymph node tissue at a single site or throughout the body (Castleman et al. in Cancer 9:822-830, 1956). It involves hyperproliferation of specific B cells that produce the cytokine IL-6. This disorder is often undiagnosed or misdiagnosed. For this reason, only very few patients have been reported, and little information is available in the literature. In hopes of providing a better understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 25 publications
6
44
1
6
Order By: Relevance
“…A total of 5 patients who underwent laparoscopic surgery achieved faster recovery, which was due to the advantage of laparoscopy in gaining access to difficult areas of the abdomen, as well as improved visualization with bloodless dissection. No patients underwent complete excision received further therapies as no evidence of disease recurrence was discovered in these patients, which was consistent with other reports on the critical role of surgical excision in UCD treatment (15,17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A total of 5 patients who underwent laparoscopic surgery achieved faster recovery, which was due to the advantage of laparoscopy in gaining access to difficult areas of the abdomen, as well as improved visualization with bloodless dissection. No patients underwent complete excision received further therapies as no evidence of disease recurrence was discovered in these patients, which was consistent with other reports on the critical role of surgical excision in UCD treatment (15,17).…”
Section: Discussionsupporting
confidence: 91%
“…HVCD has been reported in 90% of patients with UCD, but rarely in patients with MCD, whereas PCCD has been reported in only 10% of patients with UCD and in 80-90% of patients with MCD (9). In the present study, the HV type was identified in 81.5% of patients with UCD, and the PC type was observed in 57.1% of patients with MCD which was slightly lower compared with one recent study from China (17). The histological characteristics of HVCD consisted of distinctive dysplasia follicles with regressed germinal centers and a broad mantle zone of lymphocytes, which formed a concentric ring (known as the ʻonion-skinʼ arrangement) (18).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Ye et al [12] conducted a retrospective study of 52 patients with Castleman's disease between 1999 and 2008. 48 patients had UCD and in 22 cases the lesion was located in the mediastinum.…”
Section: Resultsmentioning
confidence: 99%
“…Aunque no se considera una lesión neoplásica, la variante de CP multicéntrica es tratada como tal y está asociada a riesgo incrementado de desarrollar linfoma difuso de células grandes B y sarcoma de Kaposi 3,5,6 . La EC HV frecuentemente es unicéntrica 7 y, aunque poco frecuente, se puede asociar con la aparición de sarcomas de células dendríticas foliculares de manera sincrónica o metacrónica 8,9 . Hay informes de la expresión del receptor del factor de crecimiento epidérmico (EGFR, por sus siglas en inglés) en las CDF de ambas variedades, y se ha propuesto una posible relación patogénica 2,8,9 .…”
Section: Introductionunclassified